Effectiveness of an educational intervention on knowledge and attitude on care of the environment in high school students from the school of application Unheval - Huánuco 2014 - Villanueva-Villar, Carlos (2019)
Objective. Determine the effectiveness of an educational intervention on knowledge and attitude on care of the environment. Methods. A quasi-experimental study was held with 32 high school students in the experimental group and 32 in the control group, from National School of Application UNHEVAL, during 2014. A questionnaire of knowledge and attitude scale was used to collect data. The T Student test not related was used for the inferential analysis. Results. After the intervention, major average qualifications of knowledge on care of the environment were reached in the experimental group (14.6 + -2.3) regarding the control group (10.1 + 2.6) and higher average scores were found in attitudes in general towards the conservation of environment in the experimental group (121.9+-28.6) compared to the control group (78.5+8.7). These results were statistically significant (p≤0.000). Conclusions. After the educational intervention major averages qualifications of knowledge and higher scores in attitudes on care of the environment were achieved.